Varieties of System Transformations and Their Structural Background Based on the IPS Model - Mária Csanádi (Hungarian Academy of Sciences, Institute of Economics, 2011)
This study is the theoretical chapter of a planned book. This book, aims to contribute to the theoretical foundations of similarities and differences in the transformation of party-state systems. Analytical framework of system transformation is based on the extension of the Interactive Party State model (Csan di, 2006) where specifics of the structure and operation of party-state systems and structural background of their disparities were described and analyzed. Self-similarities and disparities of transformation and path-dependency of the variety of systemic outcomes are assigned to structural characteristics of power distribution of party-state systems interpreted as networks. The empirical part of the book uses the Chinese case to test this theory, measuring the dynamics of system transformation, the consequences of short- and long-term external adaptation pressures on the system transformation and long-term consequences of the short-term reactions to these pressures and their spatial disparities. This research was supported by the National Research Foundation in Hungary.
Keywords: P2; F5; P21; P26; P30; 330; system transformation; economic transformation political transformation; sequence of transformation; disparities of transformation; varieties of system outcomes; party-state network; Systemtransformation; Theorie